Multiaffiliation: Constructive reflections - Repiso, Rafael; Aguaded, Ignacio; Montero-Díaz, Julio (Anuario ThinkEPI, 2023)
In recent weeks, there has been controversy surrounding multiple affiliation due to several scandals that have arisen in the Spanish scientific sphere. In Spain, this practice is not regulated and is incompatible with the exclusivity required by public administration for its full-time contracts. This article analyzes the positive and negative aspects that this practice has for the institutions and the academics who apply it. Likewise, a series of recommendations are made on how institutions could generate agreements in which all actors benefit from multiple affiliation while at the same time avoiding fraud. The authors of the paper conclude that this practice, developed in an honest and agreed upon manner with the institutions involved, promotes outstanding advantages. In the Spanish case, it is necessary to regulate these practices in public universities within the framework of individual agreements and conventions.